2013
DOI: 10.1111/psyg.12021
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol improves cognitive function in patients with mild cognitive impairment: a retrospective analysis

Abstract: Background and purpose: Cerebral ischemia and accumulation of amyloid β (Aβ) are major risk factors for the development of dementia, including vascular dementia and Alzheimer's disease. Cilostazol, an antiplatelet drug, has been shown to improve cerebral circulation and reduce accumulation of Aβ. In this study, the long-term effect of cilostazol on cognitive function was investigated retrospectively. Methods: Medical records at Sumotoitsuki Hospital were surveyed to find all patients treated with cilostazol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 10 publications
0
57
0
Order By: Relevance
“…The PDE3 inhibitor cilostazol was tested in several studies and indications were found that it could improve cognition, in particular in MCI/mild AD patients (e.g. [34,38,39]). The PDE4 inhibitor MK-0952 was given to patients with mild to moderate AD [77].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PDE3 inhibitor cilostazol was tested in several studies and indications were found that it could improve cognition, in particular in MCI/mild AD patients (e.g. [34,38,39]). The PDE4 inhibitor MK-0952 was given to patients with mild to moderate AD [77].…”
Section: Resultsmentioning
confidence: 99%
“…for the prevention of stroke or peripheral artery disease) reported that average daily doses above 100 mg for at least 6 months improved MMSE scores in MCI patients [38] and mild AD patients as add-on to 10 mg donepezil per day [39]. The same research group at the National Cerebral and Cardiovascular Center Hospital (Osaka, Japan) has started a new study investigating the effects on MMSE scores of cilostazol 50 mg twice a day for 96 weeks in patients with MCI (ClinicalTrials.gov identifier: NCT02491268).…”
Section: Phosphodiesterasementioning
confidence: 99%
“…A previous study has also indicated beneficial effects of cilostazol in a mouse model relevant to AD through increased amyloid β clearance due to improved cerebrovascular function 31 . Retrospective clinical studies indicated the potential for cilostazol treatment to suppress cognitive decline in elderly patients with mild dementia or cognitive impairment 32, 33 . However the current study suggests that whilst cilostazol improves hypoperfusion- induced memory deficits these are not completely restored, the improvement in memory plateaued after 12 days of testing.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot study for 10 patients with moderate Alzheimer's disease (mean Mini-Mental Examination (MMSE) score, 11.9 points) who received donepezil, cilostazol add-on treatment for 5–6 months demonstrated significantly increased MMSE score in comparison to baseline [11]. Moreover, cilostazol was shown to be effective in halting cognitive decline in patients with AD with cerebrovascular diseases [12] and mild cognitive impairment [13].…”
Section: Introductionmentioning
confidence: 99%